A Telemedicine Management Model Based on Message-Trigger Service - Hu, B.; Bai, J.; Ye, D. (Methods of Information in Medicine, 2000)
A telemedicine system model, based on a message-trigger service, is described. This model distributes system applications on multiple computers and establishes a communication platform to exchange messages among all applications. By broadcasting event messages, an application is able to trigger a set of local and remote services. At the same time, a protocol for message exchange is proposed to fulfill cooperation of applications. To validate the model, a teleconsultation system is designed. The results indicate that the model has good compatibility and that the characteristics are easy to implement.
Keywords: Telemedicine; Multipoint Communication; Message Trigger